(3OjhGf LQjQs - (3LQjQ , LQjQ Hf YWjg Hf MPjag GdNWaj Hf HOQ GdcdHj GdjQHhYj,J (B110 (3g` s ((3jGbhJ GdeSJYUei s)
(3ChdgG (B:s
(3bGd CHh SYjO GdScQi bGd LQjQ jgLh GdCNWd Mi GdYOGI HQeI GdCXdGA dGQSekG JMeO Cgdg aCMGdG s
(3BNQgG (B:s
(3ef bUjOI HGFjI ChdgG (B: (3dh cfJ ai YeOGJ Ch ai YeGjI s
(3HgG fXGe GdJYbjHIs
(3QhGjI GdScQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B119 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B129s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs